Employee Performance and The Influence Of Motivation, Discipline, And Loyalty - Indira Basalamah; Muhammad Carda P; Nizmah A.Bahasoan (Pusat Riset dan Inovasi Nasional, 2023)
Finding out what effect motivational, disciplined, and loyal attitudes have on employee performance when used in the workplace was one of the authors' research objectives. The study was conducted at the Makassar Regional Office of the Ministry of Social Affairs, which had 52 persons working there. Research of this kind was quantitative. The major data used are responses obtained from delivering surveys to respondents, which were collected through observation and questionnaires. Multiple linear regression is the test type used. In the past, several research tests were conducted, such as instrument tests composed of validity and reliability tests. The Effects of Loyalty, Motivation, and Rules on Employee Performance.